Biodiversity Credits as an economic instrument for preservation: Challenges linked to their implementation and expectations for COP-30 (Revista ESASP - Revista Científica Virtual da Escola Superior de Advocacia da OAB/SP, 2025)
This study examines biodiversity credits in the context of the Kunming-Montreal Global Framework, drawing critical parallels with carbon markets and anticipating the implementation challenges that will be debated at COP-30.(Received: October 2025 | Accepted: November 2025)
Keywords: Biodiversity Credits; Carbon Market; Kunming-Montreal; Economic Instruments; Environmental Preservation